The 1Touch Project: A Pilot Study of a Program to Teach Individuals who Are Visually Impaired Self-Defense. (July 2018) - McCarthy, Tessa; Brown, Miranda D.; Nicholls, Stephen H.
Introduction: This pilot study evaluated the percentage of skills participants in the 1Touch Project Coaching Certification Course mastered after intensive training, as well as the maintenance of these skills six months after the initial training session. In addition, the potential psychosocial benefits of the training were evaluated. Methods: In this posttest-only, pre-experimental study, participants with visual impairments (that is, those who are blind or have low vision) were trained in skills, and observers assessed the accuracy of participants on each of 76 skills. Participants completed surveys before and after training to indicate self-perceived psychosocial growth as a result of participating in the training. Results: On average, participants mastered 84.75% of the 76 steps involved in the key skills of the 1Touch program, with a range of mastery from 60.53% to 100.00%. When assessed six months after the initial training, the average level of skill mastery was 89.68%, with a range of 53.95% to 100.00%, indicating there was not a noteworthy decline in the skills that had been mastered just after training. The return rate on the surveys measuring psychosocial benefits was too low to allow accurate statistical analysis, but potentially promising trends were identified based on the increased average response from pretest to posttest. Discussion: These benefits were achieved after a brief training that could be conducted in virtually any geographic location with relatively few resources. Implications for practitioners: Providing accessible instruction in self-defense using a program like 1Touch may lead to both physical and psychological benefits.